Fodor's New Orleans, 2009 - Eisenberg, Paul.; Nalepa, Michael; Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A current travel guide to New Orleans that provides information on the city's hotels, restaurants, historical sites, popular landmarks, festivals, attractions, and activities.
Includes index.
Young Adult
Keywords: New Orleans (La.) -- Guidebooks; New Orleans (La.) -- Guidebooks